Introduction to the Advanced Multi-electrode Electrical Sounding Method - Minh, Vu Duc; Chung, Do Anh (VNU Journal of Science: Mathematics - Physics; Vol 31 No 3, 2015)
The Improved Multi-electrode Electrical Sounding method proposed by us in 2010 is a result of the research which is integrated with the reasonable private pre-eminent of the Multi-electrode Electrical Sounding and the Improved Electrical Sounding methods proposed since 2001. However, this method has just stopped in the investigation, analysis of 1D data. The article shall present the results reached after research process, that is introduction of the Advanced Multi-electrode Electrical Sounding method applied for the investigation and analysis of 2D data on the basis of using the SuperSting R8/IP system with 56 take-out and self-built software combined with EarthImager or Res2D software. Keywords: Multi-electrode Electrical Sounding, electrode array, controlling file.